Modernization of Traditional Food Processes and Products - McElhatton, Anna.; El Idrissi, Mustapha Missbah; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2016)
This volume of the Trilogy of Traditional Foods, part of the ISEKI Food Series, describes important aspects of the production of foods and beverages from all over the globe. The intention of this volume is to provide readers with an appreciation of how products were initially made, and which factors have shaped their development over time. Some modern products have remained local, while others are commodities that appear in peoples' cabinets all over the world. Modernization of Traditional Food Processes and Products is divided into two sections. The first section focuses on products originating in Europe, while the second section is a collection of products from the rest of the world. Each chapter describes the origin of a particular food or beverage and discusses the changes and the science that led to the modern products found on supermarket shelves. The international List of Contributors, which includes authors from China, Thailand, India, Argentina, New Zealand, and the United Kingdom, attests to the international collaboration for which the ISEKI Food Series is known. The volume is intended for both the practicing food professional and the interested reader.
Part I: Europe -- 1. Traditional Polish curd cheeses -- 2. Túró Rudi" - everyone's favourite milk dessert in Hungary -- 3. Quark. A traditional German fresh cheese -- 4. Modernization of the traditional Irish Cream Liqueur production process -- 5. Modernization of Skyr processing - Icelandic acid-curd soft cheese -- 6. Karachay ayran: from domestic technology to industrial production -- 7. German bread and related process technology -- 8. Production of Pastas with Bread Wheat Flour -- Part II: Americas and the Rest of the World -- 9. Edible coatings, a novel preservation method for nuts -- 10. Kaanga wai - development of a modern preservation process for a traditional Maori fermented food -- 11. Thai Fish Sauce - a traditional Fermented sauce -- 12. Yunnan Fermented Bean Curds: Furu (Lufu) -- 13. Tempe from Traditional to Modern Practices -- 14. Modernization of the Manufacturing Process for Traditional Indian Dairy Products -- 15. Yunnan Pu-erh Tea.
Keywords: Food science; Food -- Microbiology; Nutrition .; Food Science; Food Microbiology; Nutrition